Investigating the interrelationship between teachers' grading practices and classroom-based assessment strategies among Malaysian preservice teachers / Shahazwan Mat Yusoff ... [et al.] - Mat Yusoff, Shahazwan; Mohamad Marzaini, Anwar Farhan; Mat Jusoh, Ahmad Muhaimin; Zynuddin, Siti Nadya; Basal, Mohd Helme; Zakaria, Noorhayati (Universiti Teknologi MARA, 2025)
Within the Malaysian educational landscape, the grading practices and classroom-based assessment strategies adopted by preservice school teachers have become a crucial area of investigation as they may significantly impact students' academic achievements and overall learning experiences. The primary aim of this study is to explore the relationship between teachers' grading practices (TGP) and CBA practices among preservice school teachers. TGP encompasses five dimensions: Importance (IMPC), Student Effort (STUE), Student Ability (STUAB), Usefulness (USE), and Teachers' Grading Habits (TGH). A quantitative research design, specifically a survey-based approach, was employed in this study. The instrument was developed and validated through face and content validity, a pilot study, and Exploratory Factor Analysis (EFA). The quantitative data were primarily analysed using Partial Least Square Structural Equation Modelling (PLS-SEM). A total of 338 preservice teachers from 4 public universities in Selangor participated in the study, completing a 5-point Likert-scale questionnaire. Findings indicate that among the five dimensions, IMPC, STUE, and TGH significantly influence CBA practices, whereas STUAB and USE do not. The results suggest that preservice teachers prioritise student effort and well-established grading habits in their assessment strategies, reinforcing the importance of structured and transparent grading approaches. However, the limited impact of student ability and perceived usefulness on CBA implementation highlights the challenges of aligning grading practices with educational assessment frameworks. This study contributes to the understanding of grading practices in Malaysian teacher education by identifying key factors that shape assessment decisions. The findings highlight the need for continuous refinement of assessment strategies to ensure consistency and fairness in student evaluations.